Values of the Mappake’de Boyang Ethnic Mandar Tradition in Dakwah - Muammar, Muammar; Arifuddin, Arifuddin; Khalik, Abdul (Jurnal Mercusuar, 2021)
This study aims to reveal the values of da’wah in the Mappake’de Boyang culture. This is a qualitative research of library research type, where data is collected through direct or indirect quotation and analyzed using content analysis of various representative and relevant books on the topic, and then reviewed and concluded using phenomenological approach. The results of this study show that the values of da’wah in the Mappake’de Boyang culture contain values of fostering kinship, brotherhood, mutual cooperation, and barazanji da’wah values. Basically, when these values are internalized into Islamic teachings, these values are not contradictory to Islam because Islam already contains fundamental principles of individual and social relationships.